The Childfree Phenomenon: A Critical Analysis from the Perspective of Maqasid al-Nikah - Arief Hanif, Hamdan (Muwafaqat: Journal of Islamic Law, 2025)
The childfree phenomenon—defined as a deliberate choice by married couples to not have children—has significantly increased in recent years. Economic pressures, fear of parental responsibility, lifestyle changes, and rising individualism are among the primary contributors to this trend. This study critically examines the childfree phenomenon through the lens of Maqasid al-Nikah, a subcategory of Maqasid al-Shari’ah. This research employs a normative approach by analyzing Qur’anic verses, prophetic traditions, classical jurisprudential texts, and contemporary scholarly literature. The findings reveal that the essential purposes of marriage in Islam include hifz al-nasl (preservation of lineage), tranquility (sakinah), lawful fulfillment of biological needs, and the establishment of the family as a moral-educational institution. Permanent childfree decisions contradict the maqasid of marriage because they negate the objective of lineage preservation. However, temporary childfree decisions are permissible under valid reasons, such as health concerns or considerations of genuine necessity. This study highlights the importance of an educational and empathetic approach to guide younger generations toward reproductive decisions aligned with Islamic values.